2002
DOI: 10.1046/j.1442-200x.2002.01586.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance of increased serum hyaluronic acid in juvenile rheumatoid arthritis

Abstract: In children presenting with joint symptoms, serum HA measurement is useful for diagnosing systemic and polyarticular JRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Our control and experimental values for serum hyaluronan levels are similar in average values and in range to those found in previously published studies of children aged 1-18 years (Andersson and Fasth 1994;Kumar et al 1989;Shigemori et al 2002) and similar to those found in normal middle-aged adults (Laurent et al 1996), including the study of WS patients (Tanabe and Goto 2001). Examination of serum hyaluronan concentration yields values with much less variability than urinary hyaluronan and eliminates potential renal or bladder influences.…”
Section: Discussionsupporting
confidence: 88%
“…Our control and experimental values for serum hyaluronan levels are similar in average values and in range to those found in previously published studies of children aged 1-18 years (Andersson and Fasth 1994;Kumar et al 1989;Shigemori et al 2002) and similar to those found in normal middle-aged adults (Laurent et al 1996), including the study of WS patients (Tanabe and Goto 2001). Examination of serum hyaluronan concentration yields values with much less variability than urinary hyaluronan and eliminates potential renal or bladder influences.…”
Section: Discussionsupporting
confidence: 88%
“…An exception an increase of HA level in JIA children was found [14,15]. The authors suggest that serum HA measurement is useful for diagnosing systemic and polyarticular JIA [14,15]. We are of similar opinion since we proved that treatment leading to the achievement of clinical improvement in children simultaneously contributes to normalization of this GAG concentration.…”
Section: Discussionmentioning
confidence: 58%
“…However, we cannot compare our results with those obtained by other researchers since the profile of plasma GAGs has not been estimated in children with JIA so far. An exception an increase of HA level in JIA children was found [14,15]. The authors suggest that serum HA measurement is useful for diagnosing systemic and polyarticular JIA [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…However, in states of ongoing inflammation and fibrosis, such as sarcoidosis, chronic bronchitis, and idiopathic pulmonary fibrosis, there is ongoing tissue destruction and remodeling leading to persistence of HA degradation products (4,33,41). Although the precise physiologic concentration of LMW HA is unknown, during inflammation, there is increased overall HA as reflected in the serum (patients with rheumatoid arthritis, 150 ng/ml; patients with liver failure, 390 ng/ml; healthy control subjects, 36 ng/ml) and BAL (patients with sarcoidosis, 430 mg/ml) (33)(34)(35). Similarly, during inflammation and tissue destruction, adenosine is released into the extracellular space and can act as a negative regulator of both inflammation and immune-mediated tissue destruction (9,11).…”
Section: Discussionmentioning
confidence: 99%